Current Practice Pattern for Dry Eye Patients in South Korea: A Multicenter Study - Song, Jong Suk; Hyon, Joon Young; Lee, Doh; Chung, Euisang; Choi, Chulyoung; Lee, Jeongbok; Kim, Hyo Myung (Korean journal of ophthalmology, 2014)
To assess current practice patterns for dry eye patients in South Korea and to evaluate the preference according to the ages and clinic types of physicians. Dry eye patients (n = 1,612) were enrolled in this multicenter cross-sectional, observational study. The severity level of dry eye patients was classified based on the Korean guidelines for dry eye treatment. The medical records of the enrolled dry eye patients were evaluated, and the practice styles and the preferences were analyzed according to the ages and clinic types of physicians. Of all patients, dry eye level 1 was most common (47.5%), followed by level 2 (33.5%), level 3 (9.1%), and level 4 (1.1%). Topical anti-inflammatory agents were used in 70.7% of patients with dry eye level 2 and in 80.6% of patients at levels 3 and 4. Topical anti-inflammatory agents were also used in 48.7% of patients with dry eye level 1. Preservative-free artificial tears were preferred at all dry eye levels. The use of topical anti-inflammatory agents did not differ with investigator ages, but older physicians preferred preserved artificial tears more than younger ones. Physicians at referral hospitals also tended to use topical anti-inflammatory agents and preservative-free artificial tears earlier, beginning at dry eye level 1, than those who worked at private eye clinics. Topical anti-inflammatory agents were commonly prescribed for the treatment of dry eye patients in South Korea, even from dry eye level 1. Preservative-free artificial tears were preferred at all dry eye levels. Practice styles differed somewhat depending on the ages and clinic types of physicians.